Pengaruh Epoxy Terhadap Sifat Mekanik Beton Dengan Bahan Tambah Kaca Sebagai Substitusi Agregat Halus - LISANTONO, Ade; TANDEAN, Evander (Fakultas Teknik Universitas Katolik Santo Thomas, 2019)
y concrete consists of cement, water, sand and gravel. To increase the adhesion of concrete materials is adding epoxy to the concrete. While, to make the concrete has a good in water-resistant is adding glass powder which is expected to fill the air cavity in the concrete. This study aims to determine the adhesion of epoxy to glass with aggregates in a concrete ixture. Substitution of fine aggregate with glass powder is 50% by weight of fine aggregate and the use of epoxy is 10% by weight of cement. Test specimens were cylindrical with the size of (150 × 300) mm. Specimens with the size of (500 × 100 × 100) mm were also made. The Tests were carried out at the age of 14 and 28 days of concrete. Three variations were made, namely normal concrete, concrete with glass powder, and concrete with glass powder plus epoxy. The test results show that the substitution of glass powder can improve the mechanical properties of concrete, while the addition of epoxy does not significantly influence the mechanical properties of concrete with glass powder.